Evolutionary convergence of muscle architecture in relation to locomotor ecology in snakes. Issue 5 (2nd February 2023) - Mathou, Adrien; Bonnet, Xavier; Daoues, Karim; Ksas, Rémi; Herrel, Anthony
Abstract: The epaxial muscles in snakes are responsible for locomotion and as such can be expected to show adaptations in species living in different environments. Here, we tested whether the structural units that comprise the superficial epaxial muscles (semispinalis‐spinalis, SSP; longissimus dorsi, LD; iliocostalis, IC) were different in animals occupying similar habitats. To do so, we analyzed and compared the muscle architecture (mass, fiber length, and physiological cross‐sectional area) of the superficial epaxial muscle segments in snakes that differ in their habitat use (e.g., arboreal, terrestrial, and aquatic). Our results showed that arboreal species have on average longer muscles and tendons spanning more segments likely important during gap bridging. Moreover, aquatic snakes show relatively heavier semispinalis‐spinalis muscles with a greater cross‐sectional area. The longissimus dorsi muscles also showed a greater cross‐sectional area compared with terrestrial and especially arboreal snakes. Whereas the more strongly developed muscles in aquatic snakes are likely associated with the dense and viscous environment through which they move, the lighter muscles in arboreal snakes may provide an advantage when climbing. Future studies comparing other ecologies (e.g., burrowing snakes) and additional muscle units (e.g., multifidus; hypaxial muscles) are needed to better understand the structural features driving variation in locomotor performance and efficiency in snakes. Abstract : Snakes with different ecologies differ in the axial musculature with aquatic species having more robust muscles. Arboreal species on the other hand typically have longer muscle‐tendon units.